2010
DOI: 10.1016/j.otsr.2009.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Update to femoroacetabular impingement arthroscopic management

Abstract: Level IV: retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…Follow-up times ranged from 4 months to 10 years. Seven studies reported sufficient data for effect size calculation36 40 41 44 49 58 59 (tables 2 and 3). The authors of the remaining studies were contacted and six replied 3335 38 39 45.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Follow-up times ranged from 4 months to 10 years. Seven studies reported sufficient data for effect size calculation36 40 41 44 49 58 59 (tables 2 and 3). The authors of the remaining studies were contacted and six replied 3335 38 39 45.…”
Section: Resultsmentioning
confidence: 99%
“…Of 15 studies that examined the outcomes of hip arthroscopy with femoral osteoplasty (table 3), nine were prospective in design4 31 3741 49 58 and six were retrospective 30 33 34 44 45 59. Only three studies utilised comparative designs30 31 39 with the majority being case series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of patients included in the various studies was 1713, with 1141 (67%) males and 562 (33%) females, and the numbers varied from five [20] to 200 [21]. Patients were operated upon at an average age ranging from 19.7 [22] to 47.3 years [23], after an average period from one month [24] to ten years [25] from the onset of symptoms. Based on extracted data, "cam type" impingement was found in 901 hips (57.9%), "pincer type" in 74 (4.8%), and "combined cam pincer" in 580 (37.3%).…”
Section: Resultsmentioning
confidence: 99%
“…The "outcome assessment" section scored adequately in 20 articles (64.5%). Seventeen studies [9, 19, 21, 24, 26, 32-34, 36-40, 42] used the modified Harris hip score, four studies the Merle d'Aubignè scale [3,18,25,43], and five studies the WOMAC Index score [25,27,29,30,41]. The non arthritic hip score (NAHS) was used in four studies [9,23,28,33], the hip outcome score was administered in two studies [22,44], while VAS rating [26] and combined VAS and SF-12 criteria [19] were used in one study each.…”
Section: Resultsmentioning
confidence: 99%